Viewpoint: Retrospective: An Axiomatic Basis for Computer Programming. - Hoare, C. A. R. (Communications of the ACM, 2009)
The author presents his views on the use of axioms for computer programming. He reflects on the ways in which the field has changed, on the occasion of the 40th anniversary of his first published paper on the subject. He notes some of the ways in which software verification using axioms can help to guard against malware, and observes that software testing is typically more of a test of the programmer than a test of the code.